IDENTIFICATION OF PRIORITY COMMODITIES AND STRATEGIC AREAS IN THE FOOD CROPS SUBSECTOR IN TANAH DATAR REGENCY - Bahar, Erick Gunawan; Fajar Restuhadi; Arifudin (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2026)
One of the steps taken to improve the community's economy in an area is to apply a regional development strategy based on leading sectors by detecting and tracing the ability of the food crop sub-sector in an area. So that agricultural activities that are competitive and of high value provide benefits for improving the community's economy and regional income. The purpose of this research is to determine the commodities and superior areas in the food crops sub-sector in Tanah Datar Regency. The data used in this study is secondary data, namely time series data for the production of the food crops sub-sector for 5 years starting from 2017 – 2021 obtained from the Central Bureau of Statistics of Tanah Datar Regency. The commodities analyzed were rice, corn, soybeans, peanuts, green beans, cassava and sweet potatoes. The analytical methods used include Contribution Index Sectoral (CIS), Growth Ratio Model (GRM), Location Quotient (LQ), Dynamic Location Quotient (DLQ) and Composite Index (CI). The results showed that the leading food crop commodities in Tanah Datar Regency were peanuts and cassava. These two commodities are commodities that have the best average value for all sub-districts in Tanah Datar Regency. The leading areas for rice commodities are in Pariangan District, peanut commodities are in Tanjung Baru and Salimpaung Districts. The green bean commodity is located in Tanjung Emas District. Sweet potato commodity is found in Batipuh District. As for the commodities of corn, soybeans and cassava, there is not a single sub-district that forms a leading area. All identified superior areas are areas that are grouped significantly among other sub-districts in Tanah Datar District.